I love you don't die : a novel - Song, Jade (William Morrow, an imprint of HarperCollins Publishers, 2026)
"For as far back as she can remember, Vicky has been fascinated and obsessed with death as the only inevitable thing in life. From living above a Chinatown funeral parlor to working at a celebrity start-up for bespoke urns, she has surrounded herself with death--in her home, in her work, and in her ever-growing collection of zhizha, paper creations meant to be burned for the dead, adorning the walls of her apartment. Yet, though living in Manhattan and working her dream job is all she ever wanted, she still struggles to have meaningful connections--or find any meaning at all--in her life. Too often she spends the day in bed, only drawn out from time to time by her best (and only) friend, Jen. That changes when a dating app leads her into a throuple with an artist and a labor organizer, who offer exactly the kind of love she needs. For some time, it's perfect, but no one understands better than Vicky that all things must end. As doubts grow over the love in her life, her friendship with Jen, and her professional success, the oddly comforting abstraction of death starts becoming something else altogether. With everything beginning to feel hollow and temporary, Vicky must decide how to keep moving forward. To try and hold on to what she has, or to once again do what shedoes best: destroy."--